Survey of Cestode Parasites of Birds from Jalna District M. S. India - S.S. Gore; B. V. Sonune; L.V. Shinde; S.B. Pawar (International Journal of Scientific Research in Science and Technology, 2025)
The present investigation deals with the study of cestode parasites of birds from Jalna district of Maharashtra India. For the present study samples were collected from different hosts viz. Columba livia, Gallus gallus domesticus Micropus affinis. The present survey was carried out during July 2004 to June 2005. In the present study eight species were recorded which belonging to two families and six generas. viz. families Davaineidae, Barun, 1900 and Dilepdidae, Wardle, McLeod and Randinovsky, 1974.
Keywords: Survey; Parasites; Helminthes; Jalna